Biomechanical report for the IAAF World Championships London 2017 pole vault men's - Gravestock, H.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The men`s pole vault final took place on the night of August 8th. The gold medal performance was achieved by Sam Kendricks on his third attempt at 5.95 m. Piotr Lisek achieved the silver medal by clearing 5.89 m in his first attempt but he and Renaud Lavillenie failed in their attempts at the 5.95 m mark. Lavillenie, the current world record holder, also cleared 5.89 m to secure the bronze medal and achieve a season`s best performance. With only 0.06 m separating the clearance heights between gold and bronze medals, the competition to make the podium was strong. A national record was also achieved by Changrui Xue who finished 4th in the competition with a clearance of 5.82 m. (Attention! registration on the IAAF site is required for downloading)